Effects of reading strategy instruction in English as a second language on students’ academic reading comprehension - Yapp, Deborah; de Graaff, Rick; van den Bergh, Huub (Language teaching research : LTR, 2023)
The ability to read in a second language (L2) for academic purposes is essential for higher education students. Dutch colleges increasingly use materials in English or teach in English. This can be challenging for L2 readers, especially students entering higher education from vocational studies, who may have less experience with L2 academic reading. Teaching L2 reading programmes containing explicit instruction of reading strategies may benefit higher education students in L2 academic reading, particularly since reading strategies learned in the first language (L1) may not transfer to the L2. In this 7-week L2 reading strategy intervention, 801 first-year polytechnic students learned to use seven reading strategies that were effective according to a meta-analysis of L2 reading strategy studies. Data regarding students reading skills were collected over one academic year, from three treatment waves, using a regression discontinuity design. Three tests of equal difficulty were given to participants. In each wave students completed reading tests several weeks before the intervention, at the beginning and directly after the intervention. Results show that in all three waves the improvement in reading comprehension scores between the second and third measurement (due to the experimental course) significantly exceeded the increase between the first two measurement occasions. Although the intervention was shown to be effective, the effects were to some extent mediated by the previous education level. This study supports the explicit instruction of strategies in L2 reading for students in higher education and welcomes more research into L2 reading strategy interventions for students from vocational backgrounds.